The emotion of gratitude as a mediator between subjective happiness, positive and negative affect, and satisfaction with life in spanish adults - Scurtu-Tura, Maria Claudia; Fernández-Espinosa, Verónica; Obispo-Díaz, Belén (Anales de Psicología / Annals of Psychology, 2024)
This study aims to examine the predictability of satisfaction with life on the basis of subjective happiness, positive and negative affect, psychological disturbance and emotion of gratitude. It also seeks to assess whether the emotion of gratitude is a mediating variable with subjective happiness, affect, and satisfaction with life. Statistical analyses of Pearson’s correlation, multiple linear regression tests, and mediation models were conducted on a sample of 1537 Spanish adults, 73.6% were females, 26.4% males, age between 18-88 years old (M = 42.56; SD = 16.29). The emotions of gratitude were found to mediate the relationship between subjective happiness and satisfaction with life and between positive affect and satisfaction with life. Of the variables studied, positive affect is the most related to satisfaction with life, followed by subjective happiness and emotions of gratitude. Male participants are more satisfied with life when they feel the less negative affect. Regarding mediation models, emotions of gratitude mediate the relationship between subjective happiness and satisfaction with life and between positive affect and satisfaction with life. The main difference is that emotions of gratitude are stronger in females than in males.